Applying Reaction Kinetics to Pseudohomogeneous Methanation Modeling in Fixed‐Bed Reactors. Issue 6 (15th April 2020) - Scharl, Valentin; Fischer, Felix; Herrmann, Stephan; Fendt, Sebastian; Spliethoff, Hartmut
Abstract: Reactor simulations can reduce the effort when designing fixed‐bed reactors for methanation processes. Several microkinetic models were developed under a variety of operating conditions. However, most production‐scale fixed‐bed methanation processes exceed the temperature range in which these kinetic models were obtained. In addition, heat and mass transport limitations strongly influence the reaction kinetics. In this work, microkinetic rate equations for CO and CO2 methanation were analyzed with respect to their suitability for high‐temperature, pseudohomogeneous reactor modeling. The best‐suited kinetic model was fitted to the operating conditions and validated by means of CFD simulations. It is shown that the simulations match the experimental data for various operating conditions. Abstract : Complex interactions between chemical and physical processes make simulating catalytic fixed‐bed reactors challenging. Various microkinetic models of pseudohomogeneous CO and CO2 methanation at elevated temperatures were evaluated. The best kinetic model was fitted to the operating conditions and validated by CFD simulations. The simulations match experimental data for various operating conditions.